2014
DOI: 10.1136/bjophthalmol-2013-303937
|View full text |Cite
|
Sign up to set email alerts
|

The utility of routine tuberculosis screening in county hospital patients with uveitis

Abstract: PPD skin test plays an important role in the diagnosis of TB-associated uveitis in high-risk groups, such as immigrants from TB endemic regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…For some differential diagnoses, there may be insufficient material to test for all suspected pathogens. There is no commercially available kit that looks for the full breadth of most pathogens associated with endophthalmitis, which currently means that the clinician’s degree of suspicion and clinical acumen influence the pretest and posttest probabilities of certain studies [27]. Thus the advanced methods described above depend on a priori knowledge or suspicion of a particular species to choose appropriate primers, tags, and targets for analysis.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…For some differential diagnoses, there may be insufficient material to test for all suspected pathogens. There is no commercially available kit that looks for the full breadth of most pathogens associated with endophthalmitis, which currently means that the clinician’s degree of suspicion and clinical acumen influence the pretest and posttest probabilities of certain studies [27]. Thus the advanced methods described above depend on a priori knowledge or suspicion of a particular species to choose appropriate primers, tags, and targets for analysis.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…10 Nevertheless, TST is still a valuable screening tool in a high-risk population. 14 Hong et al reported a positive predictive value of TST of 17.2% for all patients and 30.3% for foreign-born patients in a retrospective study of 142 patients (prevalence of 4 and 8%, respectively). 14 …”
mentioning
confidence: 99%
“…This practice was particularly common in India. 15 While such broad screening may provide valuable information in patients in or from TB endemic regions, 2,3,8,25 and is recommended for patients with suggestive clinical features as described above 9 and prior to initiating long-term immunosuppression -particularly with tumor necrosis factor (TNF)-a inhibitors, 26 its routine use in low-risk populations use has been called into question. 27 Moreover, in both developed and developing countries, the vast majority of respondents indicated that the presence of either radiographic or immunologic evidence of prior MTB exposure would prompt them to initiate ATT, even in the absence of suggestive clinical findings.…”
mentioning
confidence: 99%